Relationship between Water Content and Mineralization of Carbon and Nitrogen in Soils Varying in Physical and Chemical Characteristics - Saidy, Akhmad Rizalli (UNIVERSITY OF LAMPUNG, 2013)
An understanding on relationship between water content and mineralization of carbon (C) and nitrogen (N) across soils varying in physical and chemical characteristics is required to assess the influence of soil physico-chemical properties on soil organic matter decomposition. However, such information is rarely available. Relationship between C and N mineralization of three soils varying in physico-chemical properties with different measurements of water content (water-filled pore space, gravimetric water content, volumetric water content, and water holding capacity) was studied through an incubation experiment for 8 weeks. Results of the experiment showed that C and N mineralization increased with increasing water content, reached a maximum, and then decreased with subsequent increasing water content levels. Maximum C and N mineralizations were observed at 70-80% and 50% water-filled pore space (WFPS), respectively. The ranges of WFPS for C and N mineralization were the narrowest among other measurements of water content. Therefore, it was likely that a single WFPS could be used in subsequent incubations to examine either C or N mineralization of soils with different characteristics. Result of this study suggests that the preliminary experiment on the relationship between mineralization of C and N and water content is necessary to do where mineralization is needed to be assessed in soils that have different physico-chemical characteristics.Keywords: Carbon and nitrogen mineralization, percent of water-filled pore space, water content[How to Cite : Saidy AR. 2013. Relationship between Water Content and Mineralization of Carbon and Nitrogen in Soils Varying in Physical and Chemical Characteristics. J Trop Soils, 18 (1) : 45-52. doi: 10.5400/jts.2013.18.1.45][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.1.45]